Assessment of mean platelet volume and soluble CD40 ligand levels in patients with non-dipper hypertension, dippers and normotensives. (February 2015) - Surgit, Ozgur; Erturk, Mehmet; Akgul, Ozgur; Pusuroglu, Hamdi; Korkmaz, Ali Fuat; Isiksacan, Nilgun; Gul, Mehmet; Uzun, Fatih; Ozal, Ender; Eksik, Abdurrahman
Abstract Objective: Patients with a lack of nocturnal decline in blood pressure (BP) are at an increased risk for cardiovascular events. Mean platelet volume (MPV) and soluble CD40 ligand (sCD40L) are accepted biomarkers of platelet activation and considered as a risk factor for cardiovascular disease. The aim of this study was to determine whether MPV and sCD40L levels are higher in non-dipper hypertensive (NDHT) patients than in dipper hypertensive (DHT) patients and healthy controls. Methods: 124 consecutive patients were included to this study. Patients were divided into three groups: NDHT patient group [n = 43; mean age 51.8 ± 6.6; 31 males (72.1%)]; DHT patient group [n = 41; mean age 50.2 ± 7.3; 22 males (53.7%)]; and normotensive group [n = 40; mean age 49.9 ± 6.7; 22 males (55%)]. Physical examination, laboratory work-up and 24-h ABPM were performed for all participants. Results: The sCD40L and MPV levels were significantly higher in the NDHT group than in the DHT and normotensive groups (p < 0.05). In correlation analysis, MPV, 24-h systolic blood pressure (SBP), 24-h diastolic blood pressure (DBP), night-time SBP and night-time DBP were positively correlated with sCD40L. Conclusion: Our study demonstrated that MPV and sCD40L levels were significantly higher in NDHT patients compared to DHT and normotensive patients. sCD40L levels were positively correlated with MPV, 24-h SBP, 24-h DBP, night-time SBP and night-time DBP.